Lembaga Penjamin Simpanan dan Fungsinya Terhadap Penyelesaian Bank Gagal di Indonesia - Zulfi Diane Zaini (KEADILAN PROGRESIF, 2012)
Trust of society to industry banking of national represent one of key to look after industrial stability of banking, so that monetary crisis goodness and also expected global crisis not recurred. Trust of society can be obtained with existence of rule of law in arrangement and observation of bank and also guarantee of bank client deposit to increase the continuity of the effort bank healthyly. If bank losing of trust of society so that the continuity of the effort such bank cannot be continued, hence such bank become Bank Fail causing to be abstracted its effort permit. On that account, owner goodness and organizer of related authority and also bank in arrangement and/or observation of bank have to work along to realize trust of society to industry bank. regulation of LPS specify guarantee of expected bank client deposit can look after trust of society to banking industry and risk minimization can encumbering State budget or risk generating moral of hazard. Guarantee of the bank client deposit carried out by LPS owning two function that is guarantying bank client deposit and partake active in looking after banking system stability as according to its.